H2S Regulation of Metabolism in Cucumber in Response to Salt-Stress Through Transcriptome and Proteome Analysis - Jiang, Jinglong; Ren, Xuming; Li, Li; Hou, Ruping; Sun, Wang; Jiao, Chengjin; Yang, Ni; Dong, Yanxin (Frontiers in Plant Science, 2020)
In a previous study, we found that H2S alleviates salinity stress in cucumber by maintaining the Na+/K+ balance and by regulating H2S metabolism and the oxidative stress response. However, little is known about the molecular mechanisms behind H2S-regulated salt-stress tolerance in cucumber. Here, an integrated transcriptomic and proteomic analysis based on RNA-seq and 2-DE was used to investigate the global mechanism underlying H2S-regulated salt-stress tolerance. In total, 11 761 differentially expressed genes (DEGs) and 61 differentially expressed proteins (DEPs) were identified. Analysis of the pathways associated with the DEGs showed that salt stress enriched expression of genes in primary and energy metabolism, such as photosynthesis, carbon metabolism and biosynthesis of amino acids. Application of H2S significantly decreased these DEGs but enriched DEGs related to plant-pathogen interaction, sulfur-containing metabolism, cell defense and signal transduction pathways. Notably, changes related to sulfur-containing metabolism and cell defense were also observed through proteome analysis, such as Cysteine synthase 1, Glutathione S-transferase U25-like, Protein disulfide-isomerase and Peroxidase 2. We present the first global analysis of the mechanism underlying H2S regulation of salt-stress tolerance in cucumber through tracking changes in the expression of specific proteins and genes.